Polish Experience in Providing Financial Aid as A Special Form of Intercommunal Cooperation and Regional Growth in The Implementation of Public Tasks - Malgorzata OFIARSKA (Communications of International Proceedings, 2022)
The issue of cooperation of local government units (especially municipalities) in order to perform public tasks is the subject of research conducted from various perspectives (mainly praxeology, economics and finance, management, political science and legal sciences). The need to conduct them is related to the search for appropriate organizational forms for the performance of public tasks by local government units and the optimal concept of managing public affairs in the sphere of public administration. Prerequisites for cooperation, diverse institutional solutions as well as the dynamics and directions of development are presented in this document. Compared to the achievements of contemporary world literature, the research on intercommunal cooperation in the countries of Central and Eastern Europe is more modest. The study was conducted using the dogmatic-legal, historical-legal and empirical methods. The study examined and assessed the provision of mutual financial assistance in Poland by entities from the local government sector (local government units, their unions and associations), recognized in the doctrine as a special and least institutionalized form of intercommunal cooperation in the implementation of public tasks. It was established that the entity granting such aid (donor) freely decides about its form and value, but in the case of granting financial aid, it should follow the rules and procedure regulated by the legislator. Financial aid may only take the qualified form of transferring funds (budgetary targeted subsidy), while in-kind aid may take more universal forms. The intended goal of the research was achieved, showing that despite inconsistent regulations in the local government law and public finance law, the interest in granting mutual financial assistance by entities of the local government sector is not decreasing. It is a permanent form of intercommunal cooperation that is used subsidiary and supplementary to perform public tasks. Its application is determined by an objective need resulting from the different level of development of individual local government units.
Keywords: local government; intercommunal cooperation; financial aid; regional growth